The compensatory effect of education as revealed by resting-state electroencephalographic alpha rhythms in patients with dementia due to Parkinson’s disease: findings from an exploratory study - Susanna Lopez; Claudio Del Percio; Roberta Lizio; Giuseppe Noce; Dharmendra Jakhar; Andrea Soricelli; Marco Salvatore; Bahar Güntekin; Görsev Yener; Federico Massa; Dario Arnaldi; Francesco Famà; et al. (GeroScience, 2025)
Here, we investigated whether educational attainment influences the neurophysiological mechanisms underlying vigilance regulation, as reflected in resting-state eyes-closed electroencephalographic (rsEEG) rhythms, in patients with dementia due to Parkinson’s (PDD) and Lewy body disease (DLB). Clinical, demographic, and rsEEG data were obtained from an international database, including PDD patients ( N = 75), DLB patients ( N = 50), and cognitively unimpaired older controls (Healthy; N = 54). Each group was partitioned into low (Edu-) and high (Edu+) educational attainment subgroups, matched for age, sex, and cognitive-motor status. We analyzed rsEEG rhythms across the individual delta, theta, and alpha frequency bands. Cortical rsEEG source topography was estimated using eLORETA freeware. In the Healthy group, Edu+ participants exhibited significantly greater widespread rsEEG alpha source activities compared to Edu- participants, possibly reflecting neuroprotective neurophysiological mechanisms. Conversely, in the PDD group, Edu+ patients showed lower widespread rsEEG alpha source activities than Edu- patients, possibly indicating compensatory mechanisms. No significant differences in rsEEG source activities were observed between DLB-Edu+ and DLB-Edu- patients. Educational attainment may be associated with compensatory mechanisms that counteract the abnormal neurophysiological processes underlying rsEEG alpha rhythms and vigilance regulation in PDD patients, but not in DLB patients. Future studies combining rsEEG and neuroimaging techniques should investigate the metabolic and functional connectivity correlates of these putative compensatory mechanisms in the PDD brain. Early education may be a key investment for national governments, especially in low-income countries, to prevent the cognitive deficits of Parkinson’s disease along aging, thereby reducing the unbearable social and economic burden.

Biopesticides provide inadequate control of three foliar bacterial diseases of tomato transplants - Inga M. Meadows; Margaret T. McGrath; Francesca Rotondo; Sally A. Miller (Crop Protection, 2023)

Biodiversity and taxonomy of the pleomorphic genus Alternaria - Daniel P. Lawrence; Francesca Rotondo; Philipp B. Gannibal (Mycological Progress, 2016)